Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 851963 species occurrences available in GBIF matching the query: { "and" : [ "Country is Mexico", "Geometry POLYGON((-98.481445 18.729501,-98.481445 15.432500,-93.757324 15.432500,-93.757324 18.729501,-98.481445 18.729501))" ] } The dataset includes 851963 records from 404 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000802-150410134957023/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences